Selection of Novel Cowpea Genotypes Derived through Gamma Irradiation - Horn, Lydia N.; Ghebrehiwot, Habteab M.; Shimelis, Hussein A. (Frontiers in Plant Science, 2016)
Cowpea (Vigna unguiculata [L.] Walp.) yields are considerably low in Namibia due to lack of improved varieties and biotic and abiotic stresses, notably, recurrent drought. Thus, genetic improvement in cowpea aims to develop cultivars with improved grain yield and tolerance to abiotic and biotic stress factors. The objective of this study was to identify agronomically desirable cowpea genotypes after mutagenesis using gamma irradiation. Seeds of three traditional cowpea varieties widely grown in Namibia including Nakare (IT81D-985), Shindimba (IT89KD-245-1) and Bira (IT87D-453-2) were gamma irradiated with varied doses and desirable mutants were selected from M2 through M6 generations. Substantial genetic variability was detected among cowpea genotypes after mutagenesis across generations including in flowering ability, maturity, flower and seed colours and grain yields. Ten phenotypically and agronomically stable novel mutants were isolated at the M6 each from the genetic background of the above three varieties. The selected promising mutants’ lines are recommended for adaptability and stability tests across representative agro-ecologies for large-scale production or breeding in Namibia or similar environments. The novel cowpea genotypes selected through the study are valuable genetic resources for genetic enhancement and breeding.